Evaluating the implementation of injury prevention strategies in Rugby Union and League: A systematic review using the RE-AIM framework - Barden, C.; Bekker, S.; Brown, J. C.; Stokes, K. A.; McKay, C. D. (International Journal of Sports Medicine, 2021)
Rugby (union and league) has come under intense scrutiny due to its injury risk. Various interventions have been introduced to protect players from injury, with many deemed efficacious and advocated for use across various worldwide contexts. However, their implementation is less clear. The objective of this systematic review was to determine whether injury prevention interventions in rugby have evaluated their `reach`, `effectiveness`, `adoption`, `implementation` and `maintenance` as per the RE-AIM Multi-Dimension Item Checklist. Six electronic databases were searched in November 2019. Inclusion criteria included: English language, peer-reviewed journal article, original research, field-based rugby code, prospective intervention. Of the 4253 studies identified, 74 met the full inclusion criteria. Protective equipment, predominately mouthguards, was the intervention of interest in 44 studies. Other interventions included multimodal national injury prevention programmes, law changes and neuromuscular training programmes. `Effectiveness` was the highest scoring RE-AIM dimension (55%), followed by `reach` (26%). All other RE-AIM dimensions scored below 20%. Research currently focuses on determining intervention `effectiveness`. For injury prevention strategies to have their desired impact, there must be a shift to address all determinants associated with implementation. Consideration should be given to how this can be achieved by adopting specific reporting checklists, research frameworks and study designs.